Pemberdayaan Masyarakat dan Keterkaitannya Dengan Peningkatan Kualitas Hiudp Masyarakat : Studi Kasus Proyek Percontohan Adaptasi Perubahan Iklim Oleh Yayasan Bintari Di Desa Tapak, Semarang - Sollistiani, Anggelini; Adi, Isbandi Rukminto (UI Scholars Hub, 2013)
This thesis discuss about an community development and its Relation with improvement quality of life through descriptive design and qualitative method. This research describes implementation pilot project as well as its relation with improvement quality of life of target community. Pilot project of planting mangrove in Desa Tapak was successfully develop tourism potential, known as ecotourism. Moreover, the ecotourism affect on increasing revenue of community itself and help improve some aspects of quality of life.